The Effect of Scaffolding of Information Literacy on the Botanical Literacy of Prospective Biology Teachers - Sari, M. S.; Sunarmi, S.; Mawaddah, K. (Jurnal Pendidikan IPA Indonesia, 2021)
The present study aims to determine the effect of the scaffolding of information literacy on the botanical literacy of prospective biology teachers. The current study employed an experimental method with a non-equivalent group design. The respondents comprised 120 students in the Biology Education Program of Malang State University (the academic year 2017/2018), divided into the control and experimental groups. Data collection was based on scaffolding information literacy among prospective biology teachers and subsequent botanical literacy tests in multiple-choice format. The botanical literacy test provides nine indicator references. Reliability testing was done using Cronbach's alpha. Data were analyzed through pre-test covariate analysis (p < 0.05) for the control and experimental groups. The present study indicates that the scaffolding of information literacy has a significant effect on botanical literacy among prospective biology teachers. The findings of the current study suggest that innovation in botany learning, in this case, the scaffolding information literacy, can improve the botanical literacy of biology education students. It is necessary to undertake learning innovation with biology education students in a professional manner to enable them to transfer knowledge using scaffolding information literacy to their prospective students. In conclusion, the scaffolding of information literacy has a significant effect on botanical literacy among prospective biology teachers.